2017
DOI: 10.1007/s12039-017-1263-9
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and their lifetimes in acetamide/electrolyte deep eutectics: anion dependence

Abstract: Extensive computer simulations with deep eutectics made of acetamide (CH 3 CONH 2) and lithium salts (LiX) have been performed at 303 K and 350 K to identify the solution-phase microstructures in these media and investigate the anion dependence of the size and lifetime distributions of these microstructures. In addition, we explore how the added electrolyte interferes with the natural hydrogen bonded (H-bonded) network structure of liquid acetamide. For this purpose several radial distribution functions have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 80 publications
(97 reference statements)
0
23
0
Order By: Relevance
“…47 DESs comprised of electrolytes and amides as HBD species have also been explored recently. 8,9 The microscopic structural arrangement and properties of DESs can be tuned by selection of mixing ratio and their constituting molecular chemical moieties. This additional degree of freedom to design DESs with desired properties is encouraging to use DESs in various fields such as inorganic and organic synthesis, separation, electrochemistry, extraction, nanomaterials science, and biotransformations.…”
Section: Introductionmentioning
confidence: 99%
“…47 DESs comprised of electrolytes and amides as HBD species have also been explored recently. 8,9 The microscopic structural arrangement and properties of DESs can be tuned by selection of mixing ratio and their constituting molecular chemical moieties. This additional degree of freedom to design DESs with desired properties is encouraging to use DESs in various fields such as inorganic and organic synthesis, separation, electrochemistry, extraction, nanomaterials science, and biotransformations.…”
Section: Introductionmentioning
confidence: 99%
“…Biswas et al [ 243 , 244 ] performed MD microstructure simulations for a number of Li salts (Li + , Br − , NO 3 − , ClO 4 − ) and acetamide to identify the solution-phase microstructures in these media, and investigated the anion and temperature dependence of these microstructures. The authors showed that the presence of heterogeneity arises from the balance of the interactions between the various species.…”
Section: Main Directions Of Investigationsmentioning
confidence: 99%
“…Mixtures of Li salts and amides are characterized by a well-studied micro-heterogeneity. 11,130,[138][139][140] The investigation of electrolytes composed Li salts (LiClO4, LiBr, LiNO3) with AA and other short-chain amides (propionamide PA and butyramide BA) via time-resolved fluorescence measurements and all-atom MD simulation revealed for instance pronounced solution heterogeneity. 11,130 In all cases the AA−ion interactions are stronger than the AA−AA ones.…”
Section: Lithium Salts and Amidesmentioning
confidence: 99%
“…130,137 The ion effect is also evident on the hydrogen bond lifetime, with AA-AA and Li + -AA clusters having higher lifetimes in presence of Br − , while Li + −X− clusters being most stable in the presence of NO3 − . 140 The nanoscale dynamics of some of these AA-based DESs (with LiNO3 or LiClO4) has been investigated by Srinivasan and coworkers using quasielastic neutron scattering (QENS) and MD simulations. [134][135][136] Results indicate that the AA molecules form a hydrogen-bond network with its neighbouring set of molecules resulting in a transient cage and the molecular diffusion of AA involves a combination of localized diffusion and cage-to-cage jump diffusion.…”
Section: Lithium Salts and Amidesmentioning
confidence: 99%